2014
DOI: 10.1097/mnm.0000000000000027
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an automated dose-dispensing system for 18F-FDG administrations and associated reduction in operator extremity dose

Abstract: The μDDS-A reproducibly partitions a vial of F-FDG and offers a significant reduction in extremity dose to the operator of up to 80% in comparison with a manual partition technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The desired volume of 18 F-FDG dispensed by each device declines as a function of a higher radioactive concentration when extracted from multidose vials (13). Therefore, a dispensed volume below 0.5 mL conspicuously worsened the administration error of the AI-300, which was already overestimated compared with the other devices.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The desired volume of 18 F-FDG dispensed by each device declines as a function of a higher radioactive concentration when extracted from multidose vials (13). Therefore, a dispensed volume below 0.5 mL conspicuously worsened the administration error of the AI-300, which was already overestimated compared with the other devices.…”
Section: Resultsmentioning
confidence: 99%
“…Further study is required to evaluate the radiation protection ability and operational aspects of automated infusion devices (4,7,12,13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These systems have a built-in reservoir for storing FDG in a sterile and shielded way, contain a dose calibrator connected with the reservoir, and have a system of tubing and pumps that are able to deliver a requested amount of activity to a shielded syringe or device ready for injection into the patient. Data has shown that these systems are accurate, deliver activities for injection within a 3% margin of that requested, combined with reductions in the radiation exposure to the hands and fingers of technologists of 80-94% compared to manual dispensing and injection (32,33).…”
Section: Automated Dispensing and Injectionmentioning
confidence: 99%
“…Since many evidences showed substantial benefits in radioprotection for the operators in terms of dosimetry, many nuclear medicine departments have equipped themselves with automated dispensing systems (ADS) (Covens et al 2010). Most of the validations found in the literature consist in monitoring physico-medical parameters such as operator dosimetry and accuracy and/or precision of dose activities measurements through dose calibrators (Lecchi et al 2012;O'Doherty et al 2014). Whether partially or fully automated, to date there is no marketed ADS representing a true "closed-system".…”
Section: Introductionmentioning
confidence: 99%